Each Hour Redeem : Time and Justice in African American Literature - English, Daylanne K. (Book collections on Project MUSE., 2013)
This book advances a major reinterpretation of African American literature from the late eighteenth to the early twenty-first century by demonstrating how its authors are centrally concerned with racially different experiences of time. The author argues that, from Phillis Wheatley to Suzan-Lori Parks, African American writers have depicted distinctive forms of temporality to challenge racial injustices supported by dominant ideas of time.